ANALISIS KELEMBAGAAN KELOMPOK PETANI TAMBAK DALAM PENGEMBANGAN USAHA BUDIDAYA (Studi Kasus di Desa Tambakbulusan Kecamatan Karang Tengah Kab. Demak) - Rachman Djamal (JURNAL LITBANG PROVINSI JAWA TENGAH, 2014)
This information is result of institutional case study in the Tambakbulusan Vilage, Karangtengah of Demak Regency. This activity is carried out between the September - December 2013. Method used in this study is dikriptif analysis using primary data (indept interview and focused group discutions) and secondary data related to the title of this research. The results showed: 1) internal institutional factors consist of strength and weaknesses affecting to the fish farmers group on optimizing fish farming in ponds it’s : the human (Board & Members of the group), the aim of organization, management board, the use of capital, and services to members; 2) external factors, namely institutional opportunities and threats (threates) affect farmers trying : the socio-cultural organization formed by the government or private sector, banking, government regulation and legislation, homogeneity farmers, and availability of technology; 3) The activities that have been carried out to develop a business group in ponds that are monokulur or polyculture fish with shrimp (Vamame) and or seaweed (Gracillaria Sp.). The results of this study recommends that efforts to increase the utilization of the pond so that the optimization can increase the production and value of production of cultured fish takes effort to increase the role of the existing fish farmers to develop the strength group to suppress weakness, avoid threats and seize opportunities group.